The main tasks of fine arts in the educational process - Jumaboev Nabi Pardaboevich; Usmanov Botir Аllaberdievich; Mamatkhonova Shahrizod Bahodir kizi (Research Parks Publishing LLC, 2021)
The article discusses the purpose of the science of fine arts, its role in the formation and upbringing of the child's worldview. It was noted that this science is inextricably linked with other disciplines, and that it is of great importance in the development of new materials in these disciplines